2010
DOI: 10.1007/s10549-010-0835-x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of retinoic acid-induced functional sodium iodide symporter (NIS) expression and cytotoxicity of 131I by carbamazepine in breast cancer cells

Abstract: Incubation with CBZ stimulated atRA-induced iodide accumulation up to 2-fold in a concentration-dependent manner, while atRA/Dex-stimulated iodide uptake was further stimulated up to 1.5-fold by additional CBZ treatment based on significantly increased NIS mRNA and protein levels. This stimulatory effect of CBZ was shown to be dependent on the PI3K-Akt pathway without involvement of mTOR. In contrast, treatment with CBZ alone had no effect on functional NIS expression. Moreover, selective cytotoxicity of 131 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
(53 reference statements)
0
16
0
1
Order By: Relevance
“…RA-induced enhancement of NIS is increased by hydrocortisone, dexamethasone, troglitazone (a peroxisome proliferator–activated receptor γ, PPARγ, agonist), histone deacetylase (HDAC) inhibitors (tricostatin A and sodium butyrate), and carbamazepine [58,62-64]. Hydrocortisone, dexamethasone, troglitazone, and carbamazepine cooperate with RA also in inducing iodine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…RA-induced enhancement of NIS is increased by hydrocortisone, dexamethasone, troglitazone (a peroxisome proliferator–activated receptor γ, PPARγ, agonist), histone deacetylase (HDAC) inhibitors (tricostatin A and sodium butyrate), and carbamazepine [58,62-64]. Hydrocortisone, dexamethasone, troglitazone, and carbamazepine cooperate with RA also in inducing iodine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches have been investigated which could increase endogenous mammary NIS expression by stimulation of putative regulators, but while some data is promising [12], [13], increased knowledge of breast cancer and mammary NIS regulatory mechanisms is required.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that together with radioiodine scintigraphic analysis of the mammary, additional analysis methods would be essential for differentiating radio-iodide transporting benign tissue from the malignant breast cancer. In future prospective approaches, once the possibility of fibroadenoma of the breast is eliminated, radio-iodide uptake in malignant cancerous tissue of the breast could be upregulated by hormone combinations (retinoids, dex, and cbz) as previously suggested by independent works of Kogai et al (2004), and Willhauck et al (2011). That could perhaps solve the problem of discrepancy between NIS expression and NIS-positive tumour radio-iodide uptake, leading to a robust expression of functional NIS in malignant breast tissue, which could then permit use of 131 I -dependent ablation strategies for curing the disease.…”
Section: Future Strategies For Development Of Nis Activity Based Diagmentioning
confidence: 90%
“…Differential levels of NIS expression may account for variable cell surface NIS levels among breast cancer samples, and particular hormone combinations may be needed to upregulate expression and activity of the symporter at higher levels for successful future theraputic or diagnostic applications involving NIS activity. Results from different laboratories have revealed that both the expression of mammary gland NIS gene at the transcriptional level, and the post-translational trafficking/localization of NIS to plasma membrane are tightly regulated in a cellular context and an extracellular stimuli dependent way (Tazebay et al, 2000;Kogai et al, 2004;2008;Dentice et al, 2004;Alotaibi et al, 2006;2010;Willhauck et al, 2011). The list of hormones that were shown to have an upregulatory effect on NIS expression in a variety of model mammary gland cell lines and in animal experiments (xenografted and normal) include lactogenic hormones (prolactin and oxytocin), steroids (estrogens), retinoids, dexamethasone (Dex), and carbamazepine.…”
Section: Modulation Of Nis Expression In Breast Cancer Cell Models Anmentioning
confidence: 99%